Financial Inclusion Via Mobile Money Services in Ghana: Drivers and the Role of Regulation - Kodom, M. (University of Ghana, 2019)
Mobile money (MoMo) has witnessed significant increase in adoption since its inception into the Ghanaian financial market in 2009. Available statistics by the Bank of Ghana show that between 2012 and 2017, the number of registered MoMo customers increased by 534%, and active MoMo customers increased by 3,119%. With this performance, it is expected that MoMo will drive financial inclusion by not only providing users with a service to make money transfers but graduating them to use other forms of formal financial services such as savings, credit and insurance. However, little evidence currently exists on the relationship between MoMo adoption and the use of formal financial services nor on the role of Central Bank regulation in facilitating MoMo deployment and adoption. For financial inclusion purposes, it is also imperative to understand the factors driving or inhibiting MoMo adoption among groups who are mostly financially excluded. This study was conducted to examine the conditions facilitating the adoption of MoMo as a tool for achieving financial inclusion. The specific objectives were to: examine the drivers of MoMo adoption and how they vary with the demographic characteristics of the individual; assess the extent to which MoMo serves as a gateway to the use of formal financial services; and explore the role of Central Bank regulation in facilitating financial inclusion in Ghana. The 2014 and 2017 World Bank Global Findex survey datasets were used. In addition to these secondary data, primary data were collected using mixed methods. A survey was conducted across the country to gather information on the drivers of MoMo adoption. In addition, in-depth interviews with five institutions were conducted to assess the role of regulation in facilitating financial inclusion in Ghana. The results of probit analyses showed that the main drivers of MoMo adoption were perceived usefulness, social influence and cost of transaction. Perceived usefulness and social influence had a positive effect on adoption, but cost of transaction reduced the probability of adoption. These factors were found to vary significantly with gender, age, education and the locality of residence of respondents. The results of a recursive bivariate probit regression analysis also showed that MoMo serves as a gateway to the ownership of an account at a financial institution. It also enhances chances of saving, but only through the MoMo wallet, not in formal financial institutions. MoMo users were more likely to obtain credit, but not from a formal financial institution. Information from the interviews revealed that a change in the initial Central Bank regulation from a restrictive bank-led approach to a liberal telco-led approach was key to bringing clarity and to providing service providers with an incentive which encouraged them to make the necessary investments critical for enhancing growth in the MoMo financial market. Despite the remarkable performance of MoMo in the financial market, users continue to face network challenges. In addition, the persistent incidents of fraud and other abuses in the system inhibit adoption and use. Bank of Ghana should take steps to identify and understand the trends and dynamics of these fraud cases in order to make policies to contain them. The activities of the telcos and their agents need to be periodically audited to ensure that they comply with the regulations. Reduction of the 2% service charges on MoMo transactions would make the service more affordable to the previous excluded. Service providers should deploy targeted services that meet the needs of the poor and the excluded to enhance financial inclusion.
PhD. Development Studies
Keywords: Financial Inclusion; Regulation; Mobile Money (MoMo)